From Bench to Boardroom The R&D Leader's Guide - Spiro, Clifford L. (Springer International Publishing, 2018)
This must-read guide offers a practical and engaging introduction to the ins and outs of R&D leadership. Innovation is a two-trillion-dollar industry, and, on top of the baseline complexity faced by any manager, the R&D or Innovation leader confronts an additional set of challenges. Armed with years of experience in roles ranging from scientist to Vice President of R&D to founder of his own company to innovation career coach, Dr. Clifford L. Spiro shares his insights on a carefully curated selection of topics. This indispensable playbook covers: Building, managing, and motivating a team Setting schedules and goals Assessing and rewarding project success Working with other departments Legal and intellectual property considerations Dr. Spiro's distinctive blend of big-picture strategic thinking and day-to-day, nitty-gritty tips (e.g., Five Great Questions For R&D Managers to Ask Every Time) is essential reading for current and aspiring R&D leaders through seasoned managers as well as anyone at an organization that has an R&D, innovation, or technology transfer component. Providing a prescriptive, in-the-trenches assessment of how to lead innovation more effectively, this book ably equips the reader to anticipate potential problems and to succeed both within the R&D department and across his or her company.